British Columbia Loggers and the Lumber Workers Industrial Union, 1919-1922 - Hak, Gordon (Labour/Le Travailleur, 1989)
Abstract In early 1919 A new union was created in British Columbia, an organization that brought together provincial loggers for the first time. Despite much initial success, the Lumber Workers Industrial Union was moribund by 1922, and it soon disappeared completely from provincial logging camps. As well as examining the grievances of the loggers, the changing nature of the logging industry, and the actions of employers, this history of the LWIU also offers insights into the character of the Canadian working class in the post-War years by highlighting the struggles of the Socialist Party of Canada, the One Big Union, and the Industrial Workers of the World to dominate the LWIU. Furthermore, this article draws out and assesses the divergent programmes of the LWIU leaders, who were aligned with the Socialist Party of Canada, and the men in the camps, exposing a fundamental gap in the post-War socialist agenda.